Pengaruh Massage Effleurage Abdomen Terhadap Penurunan Skala Nyeri Dismenore Pada Mahasiswa Prodi D-III Keperawatan Di Universitas Abulyatama Aceh - Hadawiya, Rabiatul (Nawadeepa: Jurnal Pengabdian Masyarakat, 2025)
Dysmenorrhea pain can be overcome with various alternatives, both pharmacologically and non-pharmacologically, namely effleurage massage which is one of the effective methods in reducing pain. The effleurage technique is carried out by giving gentle strokes and light pressure on the surface of the skin. The purpose of this study was to determine the effect of abdominal effleurage massage on reducing the scale of dysmenorrhea pain in D-III Study Program students at Abulyatama University. This research method uses a quasi-experimental design using a one group pretest-posttest design with a population of 26 people and a sample of 15 people, the sampling technique is purposive sampling. The study was conducted on May 27 to June 25, 2024, univariate and bivariate data analysis using the dependent t test. The results of the study before using the abdominal effleurage massage method were mostly in the moderate category, namely 10 respondents (66.7%), while after using the abdominal effleurage massage method, the majority were in the mild category, namely 8 respondents (53.3%). This shows that there is a difference of 0.600 and the difference shows a significant difference as seen from the t-count = 3.674 and t-table = 2.145 with a P-value of 0.003. It is expected that female students can utilize Massage Effleurage as a form of massage that has been proven effective in reducing menstrual pain levels, as well as the use of ergonomic therapy and does not provide side effects if used in the long term.